Exploring the factors in food marketing that influence food choice preferences in New Zealand adults : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics, Massey University, Albany, New Zealand - Hampton, Courtney (Massey University, 2025)
Background: Over the past few decades, there has been growing concern regarding modern dietary habits, particularly the overconsumption of processed, sugary, and fast foods. While various factors shape food choices, targeted marketing strategies aimed at specific population segments have emerged as a primary influence. Food marketing shapes individual preferences and choices towards food. It involves the use of television, print media, digital platforms, social media, packaging, labelling, health claims, pricing and product placement and celebrity/influencer endorsement to reinforce messages to consumers. A substantial body of evidence exists on the influence of marketing on children's food choices, but there is currently limited research focusing on adult populations. Aim: This study aimed to investigate the factors in food marketing that influence food choice preferences of adults in New Zealand (NZ). Methods: A qualitative research method was adopted in the form of semi-structured interviews to explore experiences with and influences of food marketing in NZ Adults. Data was analysed through thematic analysis where main themes across participants were recognised. 15 participants took part in this study, with two groups identified as; 18 – 44 years old (n=8) and over 45 years old (n=7). Results: Seven main themes were identified; (1) Health consciousness (2) Packaging attributes, (3) Interpersonal influence, (4) Product placement, (5) Price, (6) Exposure and influence of food marketing, and (7) Suggestions to improve marketing that promote healthier choices. The findings suggest that there are factors related to food marketing that influence food choice or preferences across multiple levels of the Ecological Model of Health Promotion. These influences exist at the individual, interpersonal, organisational, community and policy levels. Conclusion: The findings highlight that food marketing strategies influenced food choice or preferences in NZ Adults, while also presenting differences between adult generations. The findings indicate that current food marketing regulation around advertisement, as well as the heath star rating may need to be reviewed in the promotion of healthier food choices. It is important that health professionals and policy makers take this into consideration when working with the population of NZ or developing future policy or regulation surrounding food marketing.
Keywords: 321005 Public health nutrition